ANALISIS WAKTU KERJA PENGUKURAN TINGGI POHON MENGGUNAKAN KLINOMETER DAN HAGAMETER - Diah Rakhmah Sari; Ariyanto Ariyanto (Fakultas Kehutanan Universitas Mulawarman, 2018)
Tree height measurement is one part of the inventory activity of standing trees before logging which requires a relatively long time and quite expensive costs, so it needs to use a more productive measuring instrument. There are several commonly used tree height measuring instruments, including the clinometer and hagameter. This study aim is to determine the working time of measuring tree height with clinometer and hagameter. The research method used was to determine the sample tree randomly, then measured the height of each tree with the clinometer and hagameter. In addition, it also calculates the length of time the measurement of the height of each instrument by recording the start and finish time of each measurement activity carried out. The results showed that measuring the height of a tree using clinometer takes 0.68 minutes per tree in average, and using a stick meter aid takes 1.18 minutes in average, and by using haga with a scale board aids takes 0.88 minutes per tree in average. Thus the measurement of tree height by using a clinometer is faster than using haga, while measuring the height of a tree using a hagameter with a scale board is faster than a meter.